2007
DOI: 10.1111/j.1600-6143.2007.01996.x
|View full text |Cite|
|
Sign up to set email alerts
|

Combined Coinhibitory and Costimulatory Modulation with Anti-BTLA and CTLA4Ig Facilitates Tolerance in Murine Islet Allografts

Abstract: Complex interactions between positive and negative cosignaling receptors ultimately determine the fate of the immune response. The recently identified coinhibitory receptor, B and T lymphocyte attenuator (BTLA), contributes to regulation of autoimmune and potentially alloimmune responses. We investigated the role of BTLA in a fully major histocompatibility complex-mismatched mouse islet transplant model. We report that anti-BTLA mAb (6F7) alone does not accelerate graft rejection. Rather, while CTLA4Ig alone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…Triggering BTLA or deleting BTLA highly positive T cells also might have therapeutic significance. In a model of cerebral malaria, we have shown that an agonistic Ab can prevent experimental cerebral malaria (14) and others have shown that anti-BTLA can induce delayed onset of diabetes (15), decreased T cell-induced colitis (6), and prolonged allograft survival (15,16).…”
mentioning
confidence: 98%
“…Triggering BTLA or deleting BTLA highly positive T cells also might have therapeutic significance. In a model of cerebral malaria, we have shown that an agonistic Ab can prevent experimental cerebral malaria (14) and others have shown that anti-BTLA can induce delayed onset of diabetes (15), decreased T cell-induced colitis (6), and prolonged allograft survival (15,16).…”
mentioning
confidence: 98%
“…Active suppression by regulatory cells is involved in the induction and maintenance of self-tolerance (27,28), unresponsiveness (29), and hyporesponsiveness (30Y35) to allografts. Truong et al (36) have reported that treatment with anti-BTLA mAb plus CTLA-4Ig resulted in the induction of Foxp3 + regulatory T cells within long-term engrafted islets. In the adoptive transfer studies (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…There are few studies that describe the effects of anti-specific anti-BTLA reagents in vivo (as opposed to soluble HVEM-Fc which can bind to other molecules). The study by Truong et al is a novel and interesting study that describes a synergistic improvement in allograft maintenance when the anti-BTLA mAb clone 6F7 is combined with CTLA4-Fc [34]. Specifically, at day 100 post-transplant approximately 40% of the mice treated with CTLA4-Fc alone have survived and approximately 70% of the mice treated with CTLA4-Fc and the mAb 6F7 have survived.…”
Section: Discussionmentioning
confidence: 99%